Factors Influencing the Incidence of Underweight in Toddlers Aged 12-23 Months in the Working Area of Cibeureum Public Health Center (PHC): A Cross-Sectional Study - Rista Septiani; Gantini, Dede; Rismawati, Sariestya (Universitas Nahdlatul Ulama Surabaya, 2026)
Underweight is one of the health problems in children. Data from the Ministry of Health Republic of Indonesia in 2022 stated that children under two years old who suffer from underweight in Indonesia amounted to 6.2%, while those who experience severe underweight were 1.1%. This study determines the factors influencing the incidence of underweight in children aged 12-23 months in the working area of Cibeureum PHC. The study employed a quantitative approach with an analytical design, utilizing a cross-sectional design. There were 95 respondents with purposive sampling. The instruments used were a questionnaire and nutritional status measurements, as assessed by the anthropometric weight-for-age index. Data analysis used the Chi-Square test with an α<0.05. The results showed an influence of maternal education (p = 0.000), family income (p = 0.000), maternal knowledge regarding feeding (p = 0.000), and feeding practices (p = 0.000) on the incidence of underweight. However, the history of exclusive breastfeeding did not influence the incidence (p = 0.471). In conclusion, the factors affecting the incidence of underweight in children aged 12-23 months in the working area of Cibeureum PHC include maternal education, family income, maternal knowledge, and feeding practices. Meanwhile, the history of exclusive breastfeeding did not influence the incidence.